Modelling one-third field operation in the ITER pre-fusion power operation phase. (27th September 2019) - Schneider, M.; Polevoi, A.R.; Kim, S.H.; Loarte, A.; Pinches, S.D.; Artaud, J-F.; Militello-ASP, E.; Beaumont, B.; Bilato, R.; Boilson, D.; Campbell, D.J.; Dumortier, P.; et al.
Abstract: In the four-stage approach of the new ITER Research Plan, the first pre-fusion power operation (PFPO) phase will only have limited power available from external heating and current drive (H&CD) systems: 20–30 MW provided by the electron cyclotron resonance heating (ECRH) system. Accessing the H-mode confinement regime at such low auxiliary power requires operating at low magnetic field, plasma current and density, i.e. 1.8 T and 5 MA for a density between 40% and 50% of the Greenwald density. H-mode plasmas at 5 MA/1.8 T will also be investigated in the second PFPO phase when ITER will have its full complement of H&CD capabilities installed, i.e. 20–30 MW of ECRH, 20 MW of ion cyclotron resonance heating and 33 MW of neutral beam injection. This paper describes the operational constraints and the H&CD capabilities for such scenarios in hydrogen and helium plasmas, to assess their viability and the issues it will be possible to address with them. The modelling results show that 5 MA/1.8 T scenarios are viable and will allow the exploration of the H-mode physics and control issues foreseen in the ITER Research Programme in the PFPO phases.